The Role of Vakya Vidya in The Digital Era Dialogue - Sumaryani, Ni Made; Yogiswari, Krisna S.; Nurlina (Institute for Advanced Science, Social, and Sustainable Future, 2023)
Mastery of philosophy and theology is very influential in internal and inter-religious dialogue. Besides critical thinking and well-established argumentation, dialogue, debate, and discussion are central knowledge in darśana. Hindu thinkers mastered Tarka-Vāda and were able to dialogue with adherents of Sanatana Dharma and with followers of other faiths. The expertise of di Ādi Śaṅkarācārya and other Hindu thinkers in the field of Tarka-Vāda is essential today for Dharmapracārakas, teachers, Hindu Scholars, academics, and Hindu devotees. In addition, the mastery of Tarka-Vāda as an effort to support the science of communication (Vakya Vidya) in the Hindu tree of knowledge and glorify Vācaspati.